A rare mitochondrial disorder: Leigh sydrome - a case report - Shrikhande Dhananjay Y; Kalakoti Piyush; Syed MM Aarif; Ahya Kunal; Singh Gurmeet (BMC, 2010)
Abstract Leigh syndrome is a rare progressive neurodegenerative, mitochondrial disorder of childhood with only a few cases documented from India. The clinical presentation of Leigh syndrome is highly variable. However, in most cases it presents as a progressive neurological disease with motor and intellectual developmental delay and signs and symptoms of brain stem and/or basal ganglia involvement. Raised lactate levels in blood and/or cerebrospinal fluid is noted. It is the neuroimaging, mainly the Magnetic Resonance Imaging showing characteristic symmetrical necrotic lesions in the basal ganglia and/or brain stem that leads to the diagnosis. Here, we report a case of 7 months old female child presenting to us with status epilepticus, delayed developmental milestones and regression of the achieved milestones suspected to be a case of neurodegenerative disorder, which on MRI was diagnosed as Leigh syndrome.